Neonatal Clonazepam Administration Induces Long-Lasting Changes in Glutamate Receptors - Kubová, Hana; Bendová, Zdenka; Moravcová, Simona; Pačesová, Dominika; Rocha, Luisa Lilia; Mareš, Pavel (Frontiers in Molecular Neuroscience, 2018)
γ-aminobutyric acid (GABA) pathways play an important role in neuronal circuitry formation during early postnatal development. Our previous studies revealed an increased risk for adverse neurodevelopmental consequences in animals exposed to benzodiazepines, which enhance GABA inhibition via GABAA receptors. We reported that administration of the benzodiazepine clonazepam (CZP) during postnatal days 7–11 resulted in permanent behavioral alterations. However, the mechanisms underlying these changes are unknown. We hypothesized that early CZP exposure modifies development of glutamatergic receptors and their composition due to the tight developmental link between GABAergic functions and maturation of glutamatergic signaling. These changes may alter excitatory synapses, as well as neuronal connectivity and function of the neural network. We used quantitative real-time PCR and quantitative autoradiography to examine changes in NMDA and AMPA receptor composition and binding in response to CZP (1 mg/kg/day) administration for five consecutive days, beginning on P7. Brains were collected 48 h, 1 week, or 60 days after treatment cessation, and mRNA subunit expression was assessed in the hippocampus and sensorimotor cortex. A separate group of animals was used to determine binding to NMDA in different brain regions. Patterns of CZP-induced alterations in subunit mRNA expression were dependent on brain structure, interval after CZP cessation, and receptor subunit type. In the hippocampus, upregulation of GluN1, GluN3, and GluR2 subunit mRNA was observed at the 48-h interval, and GluN2A and GluR1 mRNA expression levels were higher 1 week after CZP cessation compared to controls, while GluN2B was downregulated. CZP exposure increased GluN3 and GluR2 subunit mRNA expression levels in the sensorimotor cortex 48 h after treatment cessation. GluA3 was higher 1 week after the CZP exposure, and GluN2A and GluA4 mRNA were significantly upregulated 2 months later. Expression of other subunits was not significantly different from that of the controls. NMDA receptor binding increased 1 week after the end of exposure in most hippocampal and cortical areas, including the sensorimotor cortex at the 48-h interval. CZP exposure decreased NMDA receptor binding in most evaluated hippocampal and cortical areas 2 months after the end of administration. Overall, early CZP exposure likely results in long-term glutamatergic receptor modulation that may affect synaptic development and function, potentially causing behavioral impairment.